2022
DOI: 10.3390/vaccines10060934
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a Modified Live Porcine Reproductive and Respiratory Syndrome Virus 1 (PRRSV-1) Vaccine against Experimental Infection with PRRSV AUT15-33 in Weaned Piglets

Abstract: In this study, the efficacy of the commercial modified live PRRSV-1 vaccine “Ingelvac PRRSFLEX® EU” was assessed in weaned piglets experimentally infected with PRRSV strain AUT15-33. Seventy-four weaned piglets were allocated to five groups. Vaccinated (groups 1, 2, and 5) and non-vaccinated piglets (groups 3 and 4), infected with either a low dose (103 TCID50/dose; groups 2 and 4) or a high dose (105 TCID50/dose; groups 1 and 3) of the virus, were compared regarding clinical signs, average daily weight gain (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 44 publications
1
9
1
Order By: Relevance
“…In our study, we observed viral loads in the serum of around 8 log 10 genome copies/mL (Fig. 2 a), which is in accordance with two previous studies using this isolate (Kreutzmann et al 2022 ; Dürlinger et al 2022 ). Regarding lung pathology and body temperature, we did not observe clear differences between vaccinated and infected and only infected pigs, irrespective of the DON feeding regimen.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our study, we observed viral loads in the serum of around 8 log 10 genome copies/mL (Fig. 2 a), which is in accordance with two previous studies using this isolate (Kreutzmann et al 2022 ; Dürlinger et al 2022 ). Regarding lung pathology and body temperature, we did not observe clear differences between vaccinated and infected and only infected pigs, irrespective of the DON feeding regimen.…”
Section: Discussionsupporting
confidence: 93%
“…For our study, we used a licensed PRRSV-1 MLV for vaccination and challenged with the heterologous PRRSV-1 strain AUT15-33. This PRRSV isolate has been shown to be highly virulent in experimental infection studies with growing pigs and pregnant sows (Kreutzmann et al 2021 , 2022 ; Dürlinger et al 2022 ). In our study, we observed viral loads in the serum of around 8 log 10 genome copies/mL (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The most recent isolate, AUT22-97, derives from AUT15-33 that emerged seven years ago as an outbreak with severe reproductive losses and clinical signs in nursery pigs on Austrian farms [ 37 ]. AUT15-33 is characterized extensively and shows both considerable virulence in reproductive as well as respiratory challenge trials [ 20 , 38 ]. We frequently find descendants of AUT15-33 in current clinical samples from Austria indicating high competitiveness in the field.…”
Section: Discussionmentioning
confidence: 99%
“…Immunization is an effective measure to prevent and control PRRS, in which inactivated vaccines and subunit vaccines could not provide effective protection against PRRSV (17,18). Live PRRS vaccines could stimulate cellular and humoral immune responses and provide respectable immune efficacy against heterologous PRRSV strains (19)(20)(21)(22)(23). In China, many live vaccines have been developed and used for PRRS control and contributed to the development of the pig industry (24,25).…”
Section: Introductionmentioning
confidence: 99%